EFFECT OF ASYMMETRIC CARBON FIBER SKIN LAYER DISTRIBUTION ON THE FLEXURAL STRENGTH OF POLYPROPYLENE HONEYCOMB SANDWICH COMPOSITES - Muhammad Nauval Althaaf Lovrien; Muhammad Alfatih Hendrawan (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
Advances in energy-efficient vehicle technology require lightweight materials that maintain high structural strength. One developed alternative is a polypropylene honeycomb-based sandwich composite structure reinforced with carbon fiber for monocoque chassis applications. This study aims to analyze the effect of varying the number of carbon fiber layers in the top and bottom skins on bending strength and post-test damage characteristics. Specimens were fabricated using the vacuum infusion method at a pressure of -0.8 bar, employing a polypropylene honeycomb core, 3K twill carbon fiber, and an epoxy matrix. Bending tests were conducted using the three-point bending method in accordance with ASTM D790 on three configuration variations: 5-3, 4-4, and 3-5 (top skin–bottom skin). The results showed that the configuration with 5 layers on the top skin and 3 layers on the bottom skin yielded the highest flexural strength of 15.456 MPa, followed by the 4-4 configuration at 12.469 MPa and the 3-5 configuration at 11.654 MPa. Macroscopic analysis revealed failure mechanisms including bending deformation, delamination, core crushing, matrix cracking, lower skin cracking, and fiber pull-out. It is concluded that increasing carbon fiber layers in the top skin significantly enhances flexural strength and reduces damage to the sandwich composite structure.